Pengembangan Ulangan Harian Matematika Berbasis Android Menggunakan Aplikasi Google Form - Ardiansyah, M. (Lentera: Jurnal Ilmiah Kependidikan, 2020)
This is R & D (Research and Development) research. The research and development design that researchers use the 4D model with four stages of development. The subjects in this study were students of SMK Islam Perti Jakarta Barat class XI in OTK Office 2 and OTK Office 3 with a total of 52 students. The data collection techniques used were interviews and questionnaires. With the development of android-based daily math tests using the google form application, it is easier for teachers to complete assessment administration, teachers can learn technology, get digital test scores, make it easier to perform advanced data processing related to math scores. Students are faster in receiving information from teachers, motivating the use of technological developments, can participate in learning activities anytime and anywhere.